MEDIA APLIKASI HEAGER (HEALTH TEENAGER) MENINGKATKAN PENGETAHUAN TENTANG MENARCHE - Siti Rofi'ah; Siti Chunaeni; Sri Utary Fepriyanti; Dwi Kuntari (POLTEKKES KEMENKES SEMARANG, 2023)
Adolescent physical changes related to hormonal changes, the period of sexual maturity and reactions to menarche. Low understanding of menarche can have a negative impact on adolescent growth. Technological progress is a potential that can be used as a delivery of material related to menarche. The